DEVELOPING CONFIDENCE AND ENGLISH SPEAKING SKILLS IN COLLEGE STUDENTS THROUGH STORY-TELLING TECHNIQUE - Muhammad Imran; Maria Amjad; Samina Sarwat; Naeem Ullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The current study aimed to investigate the Developing confidence and English speaking skill in college students through the story-telling technique. The strategy of storytelling was a method that helped the students to communicate in terms of improving grammar and making sense of ideas. Firstly researchermade a hypothesis and then to get the results, the researcher, therefore, carried out field research at Iqra Post Graduate College Sadiq Abad by applying techniques, namely: experimental teaching. Paired sample t-test was used to analyze the scores of pre-test and post-test and to know the significant difference between results. This was demonstrated by the increase in the mean ranking, which was shown to be higher (52.4 to 69.2). Data were examined with percentages and T-Test in SPSS. Results of this study concluded that the storytelling method has improved the speaking and confidence level of college-level students.